The effectiveness of an oral gonadotropin-releasing hormone antagonist relugolix for retained products of conception (RPOC) formed after abortion at less than 22 weeks of gestation: a retrospective study - Sasatsu, Satoko; Ono, Yosuke; Miyashita, Dai; Yoshihara, Tatsuya; Tanaka, Kota; Owada, So; Makino, Kana; Nakagomi, Akiko; Ogi, Maki; Ogasawara, Eriko; Tagaya, Hikaru; Fukasawa, Hiroko; et al. (Frontiers in Medicine, 2025)
PurposeThis study investigated the effectiveness of an oral GnRH antagonist for retained products of conception (RPOC) carrying a risk of heavy bleeding.MethodsWith IRB approval and patient consent, this retrospective study included 97 RPOC cases after miscarriage. Clinical courses of the GnRH antagonist group (n = 20) were compared with those of non-GnRH antagonist group (historical control, n = 77). Surgical intervention was performed if there is no decrease in RPOC blood flow or size after treatment initiation.ResultsThe reduction rate in the maximum RPOC diameter after treatment initiation in GnRH antagonist group was greater compared to that in non-GnRH antagonist group [50 (0–79.7)% vs. 15.4 (0–56.9)]%, p < 0.001]. The frequency of surgical intervention in GnRH antagonist group was lower (30.0%, 6/20) than that of non-GnRH antagonist group (70.1%, 54/77, p = 0.002). Multivariate analysis showed that GnRH antagonist reduced the risk of surgical intervention [adjusted-odds ratio (95% confidence interval); 0.20 (0.06–0.58), p = 0.003]. In the GnRH antagonist group, the period from RPOC diagnosis to menstrual resumption was shorter [14.5 (9–71) days] than that of non-GnRH antagonist group [26.0 (6–95) days, p = 0.002].ConclusionGnRH antagonist may be a new therapeutic candidate for RPOC.